2011
DOI: 10.1103/physrevlett.107.177403
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Size-Dependent Thermalization in CdSe Nanocrystals Using Time-Resolved Photoluminescence Spectroscopy

Abstract: We report heat dissipation times in semiconductor nanocrystals of CdSe. Specifically, a previously unresolved, subnanosecond decay component in the low-temperature photoluminescence decay dynamics exhibits longer decay lifetimes (tens to hundreds of picoseconds) for larger nanocrystals as well as a size-independent, ~25-meV spectral shift. We attribute the fast relaxation to transient phonon-mediated relaxation arising from nonequilibrium acoustic phonons. Following acoustic phonon dissipation, the dark excito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 24 publications
1
56
0
Order By: Relevance
“…To account for the fact that the transient signal has negative and positive components, the absolute value of the change in scattering (|Δ S |) is used. These kinetics are well fit to a biexponential function with time components of 86 ± 24 ps—possibly due to NC cooling as it is on the order of CdSe NC cooling 46 —and a component of 510 ± 100 ps—which we attribute to the cubic-to-orthorhombic phase transition as it is on the same order as the amorphous-to-crystalline transition in CdSe NCs 37 , the most analogous process. There may also be faster features, which would require higher-time resolution instruments to resolve.…”
Section: Resultsmentioning
confidence: 78%
“…To account for the fact that the transient signal has negative and positive components, the absolute value of the change in scattering (|Δ S |) is used. These kinetics are well fit to a biexponential function with time components of 86 ± 24 ps—possibly due to NC cooling as it is on the order of CdSe NC cooling 46 —and a component of 510 ± 100 ps—which we attribute to the cubic-to-orthorhombic phase transition as it is on the same order as the amorphous-to-crystalline transition in CdSe NCs 37 , the most analogous process. There may also be faster features, which would require higher-time resolution instruments to resolve.…”
Section: Resultsmentioning
confidence: 78%
“…Colloidal quantum dots (CQDs) are specially attractive in this context since they can be prepared over a wide spectral range in highly monodisperse form and can also be easily assembled in to compact mono/multilayered films of arbitrary density using simple methods [6][7][8]. While the optical [9][10][11] and electro-optical properties [12][13][14][15] of these materials have been well studied, the necessity to push the limits of their quantum efficiencies (QE) for various applications has intensified research in this direction [16][17][18][19][20][21][22][23][24][25][26]. Some theoretical studies [27][28][29][30] in the recent past have suggested the possibility of obtaining the strong coupling and collective emission (CE) from an ensemble of quantum emitters like CQDs, mediated by plasmons.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, this interface is difficult to access experimentally; at present the only estimates of interfacial thermal conductance for a SNC and its surroundings rely on fits to a modified effective medium theory 1 or lower-bound estimates based on characterization of thermal transport rates via optical spectroscopy. 2 Such measurements yield only averaged information regarding the thermal transport and the quality of available data is typically such that fits to effective medium theories yield estimates with 100% or greater uncertainties. 1 Theoretical modeling can provide microscopic insight into the underlying physics and guide the rational design of nanoscale materials with tailored thermal properties.…”
mentioning
confidence: 99%